THE INFLUENCE OF CADMIUM CHLORIDE ISOLATED ADMINISTRATION AND IN COMBINATION WITH COPPER OR ZINC SUCCINATE ON CARDIOGENESIS OF RATS - Shatorna, V.F.; Lomyha, L.L.; Shevchenko, O.S. (World of Medicine and Biology, 2025)
Today cadmium is one of the most common pollutants among heavy metals in the Dnipro region. The negative impact of cadmium on the human cardiovascular system throughout life is generally recognized, however, there are still few results of research into the chronic impact of cadmium on cardiogenesis and the identification of effective bioantagonists capable of exerting a modifying effect on cadmium toxicity and restoring standard indicators of heart development. We conducted a study of the effect of cadmium chloride on cardiogenesis in embryos of “Wistar” rats with chronic isolated administration and in combination with copper or zinc succinate during the entire period of female pregnancy. The removed embryos and their hearts were weighed, fixed and embedded in paraplast for further histological studies. The obtained results confirmed the general tendency of the toxic effect of cadmium on cardiogenesis, which was reflected in the delay in the formation of compact myocardium, endothelial-mesenchymal transformations and reduction of cardiogel on the 13th day of embryogenesis. On the 20th day of the experiment, an increase in the thickness of the compact myocardium of the middle part of the ventricles and uneven thickening of the atrial myocardium was observed, which plays a compensatory role in chronic hypoxia of the myocardium. In the groups of combined administration of cadmium chloride with copper or zinc succinate, an antagonistic effect of these metals was observed in relation to the cardiotoxicity of cadmium chloride, which was reflected in the reduction of myocardial hypertrophy, especially in the group of the combination of cadmium and zinc.
Keywords: heart; cardiogenesis; myocardium; cadmium; zinc; copper; rats; experiment